Higher Education Graduates’ Perceived Employability in Indonesia - Saraswati, Reni Mutiarani; Lambert, Stephanie (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2023)
The lack of empirical research concerning graduate employability, particularly within the Indonesian context, has been evident, and the availability of diagnostic tools in this field is considerably limited. This research aims to investigate the factor structure of higher education graduates’ perceived employability by utilizing the CareerEDGE development model proposed by Pool and Sewel. The research is carried out among both current undergraduate students and alumni of a higher education institution in Indonesia. A total of 223 individuals are included in the data collection process. The collected data was analyzed using reliability analysis, exploratory factor analysis, and confirmatory factor analysis. SPSS and AMOS were the statistical software employed for data processing and analysis. The findings of this study contribute to a deeper understanding of the factor structure of the perception of graduate employability and provide insights into the effectiveness of the CareerEDGE model in the Indonesian context